The Effect of Using the Word Search Inquiry Model on Conceptual Understanding and Self-Efficacy in Global Warming Physics Content - Silvia Laeli; Yusman Wiyatmo (Postgraduate, University of Mataram, 2024)
To be able to create meaningful learning, educators need appropriate learning strategies. This will have a positive impact on students. Based on the results of observations of physics learning, global warming material at SMA N 1 Bantul requires the development of formative assessment media that can support classroom learning. This research aims to measure the feasibility and influence of using the word search inquiry model on conceptual understanding and self-efficacy in global warming material. The research method used is field research including the interview process, observation and documentation. Feasibility test data analysis was carried out using Likert scale analysis and influence data analysis using paired simple t-test data analysis techniques using SPSS. This research was conducted on class X students at SMA N 1 Bantul. The feasibility test data analysis obtained was 91.04% or very feasible. The test results showed a significant effect on the pre-test and post-test data. Based on the research that has been conducted, it can be concluded that using the word search inquiry model can increase students' conceptual understanding and self-efficacy.